DIVERSIFIKASI OLAHAN CUMI KERING “CUMKRING O500” DI DESA OLIMOO’O KECAMATAN BATUDAA PANTAI KABUPATEN GORONTALO - Femy M Sahami; Sri Nuryatin Hamzah (LP2M Universitas Hasanuddin, 2020)
Olimoo’o village as a coastal village has abundant squid potential, so the group of women conducted the processing of dried squid products which are named